ICOMOS Charters on cultural tourism throughout the 50 years of the UNESCO World Heritage Convention - Gowen, Margaret; Maclaren, Fergus; Martínez, Celia; Smith-Christensen, Cecilie (Restauro Archeologico, 2023)
This paper outlines the contribution of the ICOMOS International Scientific Committee on Cultural Tourism (ICTC) to tourism management throughout the history of the UNESCO Convention Concerning the Protection of the World Natural and Cultural Heritage (1972) and traces the evolution of international standard-setting texts on tourism brought forward by ICOMOS. It presents the draft International Charter for Cultural Heritage Tourism - Reinforcing cultural heritage protection and community resilience through responsible and sustainable tourism management (2021). Its new principles are formulated to address challenges of our time, instigate change, improve practice, guide future cultural tourism development and support adaptive and responsive visitor management supporting a more resilient future.